2021
DOI: 10.3389/fcell.2021.646982
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Immune-Related Risk Signature Correlates With Immunophenotype and Predicts Anti-PD-L1 Efficacy of Urothelial Cancer

Abstract: Immune checkpoint inhibitor (ICI) treatment has been used to treat advanced urothelial cancer. Molecular markers might improve risk stratification and prediction of ICI benefit for urothelial cancer patients. We analyzed 406 cases of bladder urothelial cancer from The Cancer Genome Atlas (TCGA) data set and identified 161 messenger RNAs (mRNAs) as differentially expressed immunity genes (DEIGs). Using the LASSO Cox regression model, an eight-mRNA-based risk signature was built. We validated the prognostic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…The results showed that patients with higher TMB possessed a better prognosis than those with lower TMB. Similar findings have been observed in other cancers (40)(41)(42), highlighting the possibility that TMB might serve as a prognostic marker for guiding more efficient immunotherapeutic approaches (43). By combing with FAMGs risk score, patients with low-TMB/ high-FAMGs had the lowest survival probability than other groups.…”
Section: Discussionsupporting
confidence: 78%
“…The results showed that patients with higher TMB possessed a better prognosis than those with lower TMB. Similar findings have been observed in other cancers (40)(41)(42), highlighting the possibility that TMB might serve as a prognostic marker for guiding more efficient immunotherapeutic approaches (43). By combing with FAMGs risk score, patients with low-TMB/ high-FAMGs had the lowest survival probability than other groups.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, TAMs are associated with tumor recurrence in NMIBC patients [ 42 , 43 ]. In both NMIBC and MIBC patients, a high number of TAMs is associated with a higher risk of tumor progression [ 31 , 44 ], as well as a worse progression-free survival (PFS) and overall survival (OS) [ 27 , 29 , 35 , 45 ]. Depending on the phenotype and localization, macrophages can be associated with opposite clinical outcomes in BCa.…”
Section: Macrophages In Bladder Cancermentioning
confidence: 99%
“…Some clinical parameters, including PD-L1 expression (47), CD8+ T cells (48), TMB (32), and microsatellite instability (MSI) (49), are used to predict immunotherapy treatment efficacy. It has also been reported that an immune-associated gene signature correlates with the immunophenotype, which could predict the anti-PD-L1 effect of urothelial cancer (50). While all of these factors or signatures were based on indicators associated with the immune response, our findings suggested that RNA modification patterns could also possess potential biological functions in predicting the efficacy of immunotherapy.…”
Section: Discussionmentioning
confidence: 49%